A Capacitive Discrimination of Slaughtered and Non Slaughtered Sheep and Goat Meat - A. Mohmmmad , Roaa; Ibrahim, Taib; Begam , Mumtaj; Belal, Abdallah (2010)
This paper investigates the possibilitty of differentiating slaughtered and non-slaughtered sheep andd goat meat tissue using capacitor. The capacitor designed as twwo circular parallel plates made from platinum, after putting the tissue slice between them the oscilloscope will used to measuure the capacitance voltage with the various frequencies. Mulltisim was used to identify output voltage, capacitance, permittivity and conductivity of the meat. From simulation ressults the capacitance depends on the dielectric property and volumme of blood for the meat slice and this is lead to change in the ooutput voltage. Also the dielectric properties and output voltage were proposed for slaughtered and non slaughtered animal’ss meat at various frequencies.